A Decoding Algorithm of Resolver Based on Third-order Angle Tracking Observer - YU Kang; GUO Zhida; CHEN Lei; CHEN Jianming; ZHOU Cheng; LIU Wang (Kongzhi Yu Xinxi Jishu)
In electric drive system, resolver decoder chip is expensive and its related circuits are complicated. In order to reduce system cost, a software decoding algorithm based on third-order angle observer was proposed according to the characteristics of electric drive system which often accelerates and decelerates. Compared with the characteristic of resolver decoder chip, the algorithm has the advantage of zero steady-state error of acceleration response. This paper introduced the principle of the decoding algorithm of third-order angle tracking observer and analyzed the influence of the observer parameters on tracking angle overshoot and adjustment time. Finally, a comparative experiment was carried out between the resolver software decoder and the special chip decoder. Experimental results show that the software decoder based on third-order angle observer has high decoding accuracy, which fully meets practical engineering requirements.